A method to solve a problem of flow in a channel with two axisymmetric narrowings - Борисюк A. O. (Science-based technologies, 2018)
A method is developed to solve a problem of flow in a flat rigid channel with two axisymmetric narrowings. The method has a second order of accuracy. In the method, the Navier-Stokes and discontinuity equations are solved by integrating over the elementary volumes (in which the integration domain is divided), spatial and temporal discretization of the obtained equations, as well as subsequent linearization of the discrete relationships and adjustment of the velocity and pressure fields. The temporal discretization is carried out on the basis of the implicit three-point asymmetric backward differencing scheme, whereas the spatial one is based on the TVD-scheme and the appropriate scheme of discretization of the temporal derivatives. An appropriate iterative method is applied to solve a system of linear algebraic equations.